Syntheses and Crystal Structures of Three Copper(II) Compounds with 2‐Furoic Acid: A Dinuclear Paddle‐wheel Unit and Two Coordination Polymers Supported by Pyridyl Donor Ligands1. Issue 12 (11th August 2015) - Marinho, Maria Vanda; Faria Marques, Lippy; Maia, Daniel S.; Speziali, Nivaldo L.; Yoshida, Maria Irene; Janczak, Jan; Hörner, Manfredo; Cimini Corrêa, Charlane; Diniz, Renata; Machado, Flávia C.
Abstract: Three copper(II) complexes, [Cu2 (O2 CC4 H3 O)4 (H2 O)2 ]· H2 O (1 ), {[Cu2 (O2 CC4 H3 O)4 (bipy)2 (H2 O)2 ]· 2H2 O} n (2 ), and {[Cu(bpp)2 (H2 O)](O2 CC4 H3 O)2 · 7H2 O} (3 ) [O2 CC4 H3 O = 2‐furanocarboxylate anion, bipy = 4, 4′‐bipyridine, and bpp = 1, 3‐bis(4‐pyridyl)propane] were synthesized and their crystal and molecular structures were determined by single‐crystal X‐ray diffraction analysis. Compound1 consists on bimetallic tetracarboxylate units exhibiting a common paddle wheel structure. The paddle wheel units are connected by hydrogen bonding along the crystallographic b axis and π–π stacking interactions between the furano rings along the crystallographic c axis, giving rise to a 2D supramolecular array. Compounds2 and3 were made up in the presence of 4, 4′‐bipyridine and 1, 3‐bis(4‐pyridyl)propane ligands, respectively, to produce 1D polymeric chains by metal‐ligand interactions. The presence of other weak non‐covalent interactions in these compounds extends the systems dimensionality to form 3D supramolecular networks. Abstract :